Prevalence of oral anticoagulant therapy in clinical practice in patients hospitalized with acute ischemic stroke - E. V. Tavlueva; O. N. Savkova; E. V. Zernova; S. A. Berns; O. M. Drapkina (Российский кардиологический журнал)
Aim. To evaluate the prevalence of oral anticoagulant therapy at the outpatient and inpatient stages in patients hospitalized with ischemic stroke.Material and methods. This open observational prospective real-world study included 114 patients with atrial fibrillation (AF) hospitalized with confirmed stroke.Results. Only 26,3% of patients with AF hospitalized with a confirmed diagnosis of ischemic stroke took anticoagulants (70% — direct oral anticoagulants (DOACs), 30% — warfarin). At the same time, among those taking warfarin, only one patient had normal international normalized ratio (INR) at the time of hospitalization (INR 2,6). In all other cases, the INR was <2. Of the 105 patients discharged at the outpatient stage, 93 (88,6%) patients were prescribed anticoagulants, and in most cases — DOACs (89 (84,8%)). 4 (3,8%) patients insisted on continuing warfarin therapy. There were following reasons for not prescribing DOACs: 4 (33,3%) patients were diagnosed with acute peptic ulcer during hospitalization, 2 (16,7%) — hemorrhagic transformation of the ischemic focus.Conclusion. One of the common reasons for stroke in outpatients with AF is the refusal to take oral anticoagulants or insufficient INR control when taking warfarin.